2021
DOI: 10.1016/j.jtcvs.2019.11.127
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mid-term outcomes of endovascular repair and medical management in patients with acute uncomplicated type B aortic dissection

Abstract: Objectives: To further assess the early and mid-term outcomes of thoracic endovascular aortic repair (TEVAR) in patients with acute uncomplicated type B aortic dissection (TBAD) compared with those receiving best medical treatment (BMT). Methods: Between February 2008 and March 2018, 357 consecutive patients with acute uncomplicated TBAD were retrospectively analyzed. Among them, 191 patients underwent TEVAR, and 166 received BMT. After propensity score matching, we obtained 145 matched pairs for analysis. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 34 publications
4
52
2
Order By: Relevance
“…The authors had the ambitious idea to compare in a retrospective analysis the use of TEVAR (n ¼ 191) versus medical treatment (n ¼ 166) in patients with acute uncomplicated type B AD. As expected also from literature, 4 patients receiving TEVAR had greater early 30-day mortality, although not statistically significant. However, those receiving best medical treatment had 3 times the risk (13.7% vs 5.1% at 5 years) of late adverse events (rupture and aortic enlargement) and reintervention compared with endovascular repair.…”
supporting
confidence: 84%
“…The authors had the ambitious idea to compare in a retrospective analysis the use of TEVAR (n ¼ 191) versus medical treatment (n ¼ 166) in patients with acute uncomplicated type B AD. As expected also from literature, 4 patients receiving TEVAR had greater early 30-day mortality, although not statistically significant. However, those receiving best medical treatment had 3 times the risk (13.7% vs 5.1% at 5 years) of late adverse events (rupture and aortic enlargement) and reintervention compared with endovascular repair.…”
supporting
confidence: 84%
“…Although long-term safety and e cacy of TEVAR have been con rmed with multiple studies, 3,5,16 early adverse events still attract controversy and impede the extensive application of TEVAR in uTBAD. In 2019, Professor Adams and his colleagues 6 suggested that high-risk subgroup of uTBAD patients may bene t from early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…4 Clinical researches based on retrospective cohort suggest that TEVAR is bene cial in longterm outcomes for uTBAD. 3,5 However, there are still debates about timing and indications of TEVAR on uTBAD because of disappointing early outcomes compared with optimal medical treatment. 6 Recently, there has been a signi cant body of work which has investigated the use of systemic in ammatory marker neutrophil-tolymphocyte ratio (NLR) to both prognosticate patients and to guide treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The TEVAR group had more adverse events compared to best medical therapy in the early stage (11.7% vs 2.8%, P = 0.003), although type 1 endoleak associated with TEVAR was the most significant contributor. 41 Together, the available data suggest that uncomplicated patients with high-risk features derive the most benefit from early TEVAR. Intervention performed in the subacute phase allows for acceptable positive remodeling while mitigating the periprocedural risks associated with early intervention.…”
Section: Timing Of Tevarmentioning
confidence: 99%
“…Recent evidence, however, raises the question of whether intervention should be more aggressively pursued within the acute phase window in order to maximize aortic remodeling benefit. 35,[39][40][41]…”
Section: Timing Of Tevarmentioning
confidence: 99%